Faktor Risiko Infeksi Cacing Pada Siswa Sekolah Dasar Di Beberapa Daerah Di Indonesia Periode Tahun 2013-2020 - Tahlil, Tahlil; Sartika, Suriana Dwi; Khasyrawi Abrar, Hanan (Fakultas Kedokteran Universitas Bosowa, 2025)
Worm infection (worms) is an endemic and chronic disease caused by intestinal parasitic worms with a high prevalence, which can suck blood and nutrients in the body, resulting in reduced health and nutrition in the community. The purpose of this study was to determine the risk factors for worm infection in elementary school students in several regions in Indonesia for the 2013-2020 period. The results of research from seven journals that specifically examine matters that are related to worm infections in elementary school students in several regions in Indonesia for the 2013-2020 period, it can be concluded that the habit of washing hands, the habit of using footwear, the habit of playing on the ground, Nail hygiene has a relationship with worm infections in elementary school students in several regions in Indonesia. The conclusion of helminth infections in several regions in Indonesia for the 2013-2020 period is that there is a significant relationship between hand washing habits, the habit of using footwear, the habit of playing on the ground and the cleanliness of nails